The Comparative Abilities of a Small Laccase and a Dye-Decoloring Peroxidase From the Same Bacterium to Transform Natural and Technical Lignins - Vuong, Thu V.; Singh, Rahul; Eltis, Lindsay D.; Master, Emma R. (Frontiers in Microbiology, 2021)
The relative ability of the small laccase (sLac) and dye-decoloring peroxidase (DyP2) from Amycolatopsis sp. 75iv2 to transform a variety of lignins was investigated using Time of Flight Secondary Ion Mass Spectrometry (ToF-SIMS). The enzymes modified organosolv hardwood lignin to different extents even in the absence of an added mediator. More particularly, sLac decreased the lignin modification metric S (S-lignin)/Ar (total aromatics) by 58% over 16 hours while DyP2 lowered this ratio by 31% in the absence of exogenous H2O2. When used on their own, both sLac and DyP2 also modified native lignin present in aspen wood powder, albeit to lesser extents than in the organosolv lignin. The addition of ABTS for sLac, and Mn2+ as well as H2O2 for DyP2 led to increased lignin modification in aspen wood powder as reflected by a decrease in the G/Ar metric by up to a further 13%. This highlights the importance of exogenous mediators for transforming lignin within its native matrix. Furthermore, the addition of ABTS reduced the selectivity of sLac for S-lignin over G-lignin, indicating that the mediator also altered the product profiles. Finally, when sLac was included in reactions containing DyP2, in part to generate H2O2 in situ, the relative abundance of lignin products differed from individual enzymatic treatments. Overall, these results identify possible routes to tuning lignin modification or delignification through choice of enzyme and mediator. Moreover, the current study expands the application of ToF-SIMS to evaluating enzyme action on technical lignins, which can accelerate the discovery and engineering of industrially relevant enzymes for lignin valorization.